Analisis Laporan Arus Kas, Operasi, Investasi, dan Pendanaan pada PT Pertamina (Persero) Tbk Periode 2016–2024 - Galih Wiguna; M. Hafiz Sayidil; Rudi Sanjaya; Pinkan Febriana M. (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2026)
This study aims to analyze the financial performance of PT Pertamina (Persero) through cash flow statements covering operating, investing, and financing activities during the 2016–2024 period. The study employs a quantitative descriptive method with a financial statement analysis approach using secondary data obtained from the company’s annual reports. The analysis focuses on cash flow patterns and cash flow ratios to evaluate the company’s liquidity, investment policy, and funding strategy. The results indicate that operating cash flow fluctuated throughout the observation period but consistently became the primary contributor to maintaining the company’s liquidity and operational sustainability. Investing cash flow showed consistently negative values, reflecting the company’s commitment to long-term asset expansion and business development. Meanwhile, financing cash flow experienced significant fluctuations, indicating the company’s dynamic strategy in fulfilling funding requirements through debt and equity instruments. Furthermore, the cash flow ratio analysis revealed that three financial ratios were categorized as good, while two ratios were considered less optimal. Overall, the company demonstrated a relatively healthy financial performance supported by positive operating cash flow patterns, despite still facing challenges in managing investment efficiency and financing structure. These findings indicate that PT Pertamina (Persero) has maintained stable financial fundamentals and sustainable cash flow management during the research period.